Analisis Dimensi Dan Pola Aliran Drainase Jalan Hang Tuah Kota Duri Kecamatan Mandau Kabupaten Bengkalis - Akirman, Akirman; Siswanto, Siswanto; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Flood became the dominant problems that occurred in the city of Bengkalis Mandau Duri subdistrict. Excess water in a channel resulted in a puddle in the road surface as well as residential areas. So the need for the reduction of excess water and drain to a drainage system that does not give rise to new problems that the region and its surroundings can function optimally. This study aims to analyze the dimensions anddrainage flow patterns that occurred in Jalan Hang Tuah City Mandau Bengkalis Duri subdistrict. Kandis station rainfall data for 11 years used to determine rainfall plan to use when re 10 years and obtained plans rainfall (R24) of 116.133 mm. Of the map area rainfall runoff and discharge plans in the region count to get the dimensions of the channel plan. The results of the study indicate that the channel dimensions are smallerthan the dimensions of the plan eksistingnya channels. There are other influences that cause the area was flooded.Keywords: Flooding, drainage systems, rainfall, channel dimensions